Perbandingan BIM Dengan Konvensional Pada Hasil BQ Proyek X - Wilona Benita Megawati; Purwanto, Hari (Journal of Applied Civil Engineering and Infrastructure Technology, 2022)
The construction industry is one of the industries that are being developed in Indonesia, this is evident from the many ongoing projects, both building projects and roads and bridges. Competition in construction requires construction services to complete projects in the shortest time and at the most efficient cost possible. Before making a cost budget for the project, the volume calculation of each work to be carried out will be made and packaged in a Bill of Quantity. However, in reality there are many estimates that can enlarge the results of the Bill of Quantity calculation process so that it is not efficient. Therefore, along with the development of technology in the world of construction, the Building Information Modeling (BIM) was created which can contain all the information in a development project in 3-dimensional form. Based on this, the author will compare the results of the Bill of Quantity on the conventional method with the Building Information Modeling (BIM) method on Figure for Construction using Autodesk Revit software. Based on research conducted, Bill of Quantity using the BIM method produces a higher volume of 1.24% for concrete and 1.14% for reinforcement than Conventional method. This is due to a lack of accuracy in conventional volume calculations, so the resulting volume is inaccurate.